Detecting Asymptomatic Recurrence in Early-Stage Endometrial Cancer: The Value of Vaginal Cytology, Imaging Studies, and CA-125. Issue 8 (1st October 2016) - Lee, Jung-Yun; Kim, Ji Hee; Seo, Jung Won; Kim, Hee Seung; Kim, Jae-Weon; Park, Noh Hyun; Song, Yong-Sang
Abstract : Objective: The aim of this study was to evaluate the value of vaginal cytology, imaging modalities, and serum CA-125 in detecting asymptomatic recurrence during posttreatment surveillance for early-stage endometrial cancer. Methods: A retrospective analysis was conducted on patients with stage I to II endometrial cancer who received primary surgical treatment at Seoul National University Hospital between 2000 and 2011. Clinicopathologic characteristics and surveillance test data were obtained from medical records. The total numbers of vaginal cytologies, imaging studies, and serum CA-125 levels performed during surveillance or until recurrence were evaluated, and the number of tests needed to detect each asymptomatic recurrence was calculated. Results: A total of 389 patients were identified, together with a total of 3323 vaginal cytologies, 1025 chest x-rays, 1177 abdominal computed tomography (CT) scans, 98 magnetic resonance imaging scans, 163 positron emission tomography/CT scans, 298 ultrasonographies, and 3335 serum CA-125 results obtained during the surveillance period. Recurrence was detected in 14 patients (3.6%). Ten of these cases were asymptomatic, of which six were identified through CT scans and four were identified through elevated serum CA-125 levels. Most of the patients (7/10) with asymptomatic recurrences had localized recurrence patterns, five of whom underwent curative-intent resection and survived. The number of CA-125 tests needed to identify 1 asymptomatic recurrence was 839, whereas the number of CT scans needed to achieve the same result was 196. Other imaging modalities and vaginal cytology did not detect asymptomatic recurrence. Conclusions: For posttreatment surveillance in early-stage endometrial cancer, vaginal cytology and imaging modalities such as chest x-ray, magnetic resonance imaging, positron emission tomography/CT, and ultrasonography have low utility. Routine CT scans and serum CA-125 testing may be useful for detecting asymptomatic recurrence.